Species richness and structure variations of Scots pine forest communities during the period from 5 to 210 years after fire. - Gorshkov, Vadim V.; Bakkal, Irene J. (The Finnish Society of Forest Science and The Finnish Forest Research Institute, 2009)
Part II Biodiversity Postfire recovery of species diversity (including a number of species, entropy of species relative coverage (Shannon index of species diversity) was studied in lichen and green moss site types of Scots pine forests in the central part of the Kola Peninsula. The results obtained indicate the difference in the dynamics of characteristics of biodiversity of forest components during postfire recovery. The stabilization of separate components of forest community varies in time from 5–15 to 120–140 years after the fire. Characteristics of the dwarf shrub and herb stratum recovered and stabilized 5–15 years after fire, while the complete stabilization of characteristics of moss-lichen cover is observed in community with fire ages of 90–140 years. Species richness of tree stratum recovered 120–140 years after fire. Time of complete stabilization of species richness of the community was estimated 120–140 years after fire. The size of the area over which characteristics of the biodiversity were estimated effected the mean values and, in most cases, the character of variation of studied characteristics. Over an area of 1 x 1 m dynamics of characteristics of species diversity coincide in forests of the studied types. Regardless of forest type within the area of 100 m2 species richness recovered 30 years after the fire (i.e 3–5 times earlier than the establishment of the complete stabilization of the forest structure). That means that floristic composition of the forest remained unchanged from 30 to 210 years after the fire.